Inveksi Human Papilloma Virus (HPV) dan Pencegahannya pada Remaja dan Dewasa Muda - Agnes S. Rahayu (Jurnal Biologi Papua, 2010)
Human papillomavirus (HPV) is a significant source of morbidity and mortality worldwide. The primary risk factors for aquiring HPV are generally associated with sexual activity.  Evidence suggest that condoms provide some protection against infection and disease progression, but any genital contact is sufficient for HPV transmission.  Having more than one sexual partner often result in HPV infection.  All sexually active adolescents are at high risk for aquiring HPV.  Persistent infection with high-risk HPV types (e.g HPV 16 or 18) is considered necessary for the development cervical cancer.  Most infection are asymptomatic and are efficiently cleared by he immune system.  The lesions that caused by HPV can regress in adolescent and young adult women.  A small percentage of adolescents will develop precancerous lesions that may progress to invasive cervical cancer.  Adolescents should be given appropriate education about HPV and the dangers associated with infection.  Vaccination for HPV infection should be given for presexually active children and adolescents.Key words: human papilloma virus, adolescent, cervical cancer, vaccination.